What Are the Phylogenetic Limits to Pollinator Diversity? - Ollerton, Jeff (Journal of applied entomology (1986), 2025)
ABSTRACT Although huge progress has been made over the past 200 years in identifying the diversity of pollinators of angiosperms and other plants, new discoveries continue to be made each year, especially in tropical areas and in the fossil record. In this perspective article I address the following questions: Just how diverse are the pollinators and what are the phylogenetic limits to that diversity? Which other groups of animals, not currently known to regularly engage with flowers, might be found to be pollinators in the future? Can we predict, from the fossil record and from discoveries in under‐researched parts of the world, which animal groups might turn out in the future to contain pollinators? I also discuss why adding to our knowledge of plant–pollinator interactions is important, but also stress that an incomplete knowledge may not be a bad thing if it means that remote, inaccessible and relatively pristine parts of the world remain that way.